Developing cartoon based educative mathematics learning media on mathematical representation ability of junior high school students - Haryadi, Rahman; Hartinah, Galuh (International Journal of Trends in Mathematics Education Research, 2023)
This study aimed to describe the level of validity, practicality, and effectiveness of cartoon film-based educative mathematics learning media on the mathematical representation abilities of junior high school students. This research method was the Research and Development method using the Borg and Gall model. The research subjects were students of class VIII at the Catholic Middle School of Saint Petrus Pontianak. Participants in this study included material expert validators and media expert validators and Class VII E students of St. Petrus Catholic Middle School Pontianak. Tools of data collection used including validation sheets, questionnaires, and test questions. Based on the results of the validation of material experts and media experts, the validity of the material was set at 89.57% with very valid criteria, a practical level of 91.50% with very practical criteria, an effectiveness level of 86.67% with very effective criteria.